Lithiophilic MXene‐Guided Lithium Metal Nucleation and Growth Behavior. (18th May 2021) - Ha, Son; Kim, Daesin; Lim, Hyung‐Kyu; Koo, Chong Min; Kim, Seon Joon; Yun, Young Soo
Abstract: The positive effects of a lithiophilic substrate on the electrochemical performance of lithium metal anodes are confirmed in several reports, while the understanding of lithiophilic substrate‐guided lithium metal nucleation and growth behavior is still insufficient. In this study, the effect of a lithiophilic surface on lithium metal nucleation and growth behaviors is investigated using a large‐area Ti3 C2 T x MXene substrate with a large number of oxygen and fluorine dual heteroatoms. The use of the MXene substrate results in a high lithium‐ion concentration as well as the formation of uniform solid–electrolyte‐interface (SEI) layers on the lithiophilic surface. The solid–solid interface (MXene‐SEI layer) significantly affects the surface tension of the deposited lithium metal nuclei as well as the nucleation overpotential, resulting in the formation of uniformly dispersed lithium nanoparticles (≈ 10–20 nm in diameter) over the entire MXene surface. The primary lithium nanoparticles preferentially coalesce and agglomerate into larger secondary particles while retaining their primary particle shapes. Subsequently, they form close‐packed structures, resulting in a dense metal layer composed of particle‐by‐particle microstructures. This distinctive lithium metal deposition behavior leads to highly reversible cycling performance with high Columbic efficiencies > 99.0% and long cycle lives of over 1000 cycles. Abstract : Lithiophilic surface‐guided lithium metal nucleation and growth behaviors are studied using a large‐area Ti3 C2 T x MXene electrode containing a large number of oxygen and fluorine dual heteroatoms. The lithiophilic MXene substrate significantly affects the surface tension of the lithium metal nuclei as well as the nucleation overpotential, forming highly reversible metal clusters composed of spherical lithium nanoparticles.